Long‐Run Consumption Risk and Asset Allocation under Recursive Utility and Rational Inattention. Issue 2 (March 2016) - LUO, YULEI; YOUNG, ERIC R.
Abstract : We study the portfolio decision of a household with limited information‐processing capacity (rational inattention [RI]) in a setting with recursive utility. We find that RI combined with a preference for early resolution of uncertainty could lead to a significant drop in the share of portfolios held in risky assets, even when the departure from the standard expected utility setting with full‐information rational expectations is small. In addition, we show that the equilibrium equity premium increases with the degree of inattention because inattentive investors with recursive utility face greater long‐run risk and thus require higher compensation in equilibrium.